2013
DOI: 10.1038/ncomms2966
|View full text |Cite
|
Sign up to set email alerts
|

Zscan4 restores the developmental potency of embryonic stem cells

Abstract: The developmental potency of mouse embryonic stem (ES) cells, which is the ability to contribute to a whole embryo is known to deteriorate during long-term cell culture. Previously we have shown that ES cells oscillate between Zscan4- and Zscan4+ states, and the transient activation of Zscan4 is required for the maintenance of telomeres and genome stability of ES cells. Here we show that increasing the frequency of Zscan4 activation in mouse ES cells restores and maintains their developmental potency in long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 33 publications
11
120
2
Order By: Relevance
“…Instead, telomerase-independent mechanisms (Liu et al, 2007; Zalzman et al, 2010) may have contributed to the robust reprogramming of telomeres in Terc +/− ntESCs, which is supported by a recent report that telomeres of Terc −/− cloned blastocysts are longer than those of donor cells used for SCNT (Le et al, 2014), as well as the present study. Previously we and others have shown that Zscan4 plays important roles in telomerase-independent mechanisms for iPSC reprogramming (Amano et al, 2013; Falco et al, 2007; Hirata et al, 2012; Jiang et al, 2013; Zalzman et al, 2010). In the present work, we show that elevated Zscan4 levels are correlated with increased telomere recombination events in the Terc −/− ntESCs and that Zscan4 knockdown in these cells led to shortened telomeres, implicating the potential roles of Zscan4 in telomere maintenance of ntESCs.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, telomerase-independent mechanisms (Liu et al, 2007; Zalzman et al, 2010) may have contributed to the robust reprogramming of telomeres in Terc +/− ntESCs, which is supported by a recent report that telomeres of Terc −/− cloned blastocysts are longer than those of donor cells used for SCNT (Le et al, 2014), as well as the present study. Previously we and others have shown that Zscan4 plays important roles in telomerase-independent mechanisms for iPSC reprogramming (Amano et al, 2013; Falco et al, 2007; Hirata et al, 2012; Jiang et al, 2013; Zalzman et al, 2010). In the present work, we show that elevated Zscan4 levels are correlated with increased telomere recombination events in the Terc −/− ntESCs and that Zscan4 knockdown in these cells led to shortened telomeres, implicating the potential roles of Zscan4 in telomere maintenance of ntESCs.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the beneficial effects of Zscan4 gene expression in previous studies [31,32,35], we examined whether the small molecules enhance Zscan4 expression and preserve the genomic stability of iPSCs during reprogramming. Zscan4 promotes telomere elongation without activation of telomerase [33] and plays important roles in the maintenance of genomic stability in ESCs and iPSCs [31,33].…”
Section: Small Molecules Promote Expression Of the Zscan4 Gene Duringmentioning
confidence: 99%
“…Temporal acquisition of a 2C-specific condition is critical to restoring the developmental capacity in ESCs (Amano et al 2013). Previous studies have demonstrated that a 2C-like cell population increases in cells deficient for Kap1, Lsd1, or G9a (Macfarlan et al 2012).…”
Section: Role Of Tet Proteins In Repeat Silencing and Telomere Regulamentioning
confidence: 99%
“…Because Zscan4 and other 2C-specific genes are expressed in a small population of cells in standard ESC culture (Zalzman et al 2010;Macfarlan et al 2012;Amano et al 2013), we asked whether activation of Zscan4 in Tet TKO ESCs correlates with an increase in the Zscan4-positive cell population. To this end, we stained cells with Zscan4 antibody and then counted the number of Zscan4-positive cells by fluorescence-activated cell sorting (FACS), which revealed that Zscan4-positive cells in Tet TKO ESCs increased to around sixfold of that in wild-type ESCs ( Fig.…”
Section: Increased 2c-like Population In Tet Tko Escsmentioning
confidence: 99%
See 1 more Smart Citation